Simple and Efficient Profiling of Phospholipids in Phospholipase D‐modified Soy Lecithin by HPLC with Charged Aerosol Detection. (11th April 2013) - Damnjanović, Jasmina; Nakano, Hideo; Iwasaki, Yugo
Abstract: Dietary phosphatidylinositol (PI) can be synthesized via phospholipase D (PLD)‐catalyzed transphosphatidylation of phosphatidylcholine (PC), abundant in soy lecithin, with myo‐inositol. However, a generated mixture of phospholipid (PL) classes poses a challenge for analysis. Our current work on Streptomyces PLD engineering requires a robust analytical method for profiling of PI and related PLs derived from the transphosphatidylation reactions. Therefore, we optimized an HPLC‐based method with charged aerosol detector (CAD) for PL quantification. PLs were separated on a normal phase silica column by a gradient elution system using two solvents containing chloroform/methanol/1 M formic acid–triethylamine buffer in different ratios. Retention times of the PL standards and LC–MS under identical conditions were used to identity PL classes. PL standards gave linear response in 100‐ and 10‐fold (lyso‐PI) concentration range. The method provided a simple, sensitive, repeatable, and precise analysis of PI, PC, phosphatidylethanolamine, phosphatidic acid, and lyso forms of PC and PI. Compared to the similar existing method, introduction of CAD provided a three‐ to fivefold decrease at the lower end and a two‐ to fivefold increase at the upper end of the dynamic range. High precision, high sensitivity, and low limits of detection and quantification further underline the benefits of CAD in PL analysis.